Policy and practice - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Advances in learning and behavioral disabilities ;, 2009)
In the study of learning and behavioral disabilities, effective practice and public policy enacted to implement this practice are closely intertwined. In this volume, a number of internationally prominent authors discuss issues and advances both in public policy, and in state-of-the art practice in providing service for individuals with learning and behavioral disabilities. Topics include educational equity, imputations of malice in social policy, analytical discussions of Response to Intervention and No Child Left Behind legislation, policy implications of functional behavioral assessment, implications of poverty for educational policy, and public policy implications of the Higher Education Opportunity Act. In addition, chapters are included that address recent advances in practice for individuals with learning and behavioral disabilities. These topics include interventions for students with Attention Deficit Hyperactivity Disorder, mathematics interventions for individuals with nonverbal learning disabilities, Response-to-Intervention and other literacy practices for students with learning and behavioral disabilities, and the design of functional assessment for challenging behavior. The chapters included in this volume provide important current information on policy and practice for individuals with learning and behavioral disabilities, and will be of interest to teachers, administrators, graduate students, researchers, professionals in personnel preparation programs, and individuals interested in public policy.